ELISA-based competitive trypsin inhibition assay. Issue 1 (1st January 2021) - Ergenoğlu, Bengü; Ertekin, Özlem; Pirinçci Göktürk, Şerife Şeyda; Dinç, Göknur Gizem; Akçael, Esin; Bağirova, Melahat; Yücel, Fatıma
Abstract: Proteolytic enzymes are crucial for numerous biological processes and are tightly controlled by specific inhibitors. In addition to the research activities to investigate the natural effects of these inhibitors, it is important to determine the inhibition capabilities of inhibitors due to their importance in different fields, including food and health industry. In this study, we describe a high-throughput adaptable screening method to detect inhibitors and compare their inhibition efficiency at nanogram levels, using a Competitive enzyme-linked immunosorbent assay (ELISA) based Trypsin Inhibition Assay (E-CTIA). We worked with four different inhibitors from different sources and action mechanisms, all of which were competitive inhibitors. The half-maximal inhibitory concentration (IC50 ) strongly correlated with the experimental inhibition capacities introduced in the user manuals. E-CTIA successfully fulfills the requirements of an assay, such as reproducibility, low cost, low sample requirement and ease of use. It also enables to test multiple samples simultaneously in a short time, and it has the potential to be adapted to bigger plate formats such as 384 well or even bigger. Besides being the first successful example of Competitive ELISA Based Inhibition Assay, it has the potential to be used for many competitive inhibitors.